Tourism on The Bako National Park: peripheral issues, strategies and development - Mohamad, Aimi Zawani; Wan Rosli, Wan Nur Arifah; Md Sawari, Siti Salwa (2018)
Tourism sector has been identified as a key sector to boost Sarawak economic development. The Sarawak government regards Bako National Park as valuable resources for tourism. Thus, this paper presents an overview of the most recent peripheral issues and strategies in promoting Bako National Park. As the paper in this tourism master plan implies to and existing policies from various sources which will be used and apply as new policies in place for developer to take into consideration when implementing the initiatives according to their strategic. It is hope that this paper can contribute to the future development of Bako national Park.